Melæna massif révélant un syndrome de Peutz-Jeghers vu au CHU-JRA Madagascar: à propos d'un cas - Martinetti, Andrianimaro Florelia (Pan Afr Med J, 2016)
Peutz-Jeghers syndrome (SPJ) is characterized by intestinal hamartomatous polyps in association with mucocutaneous lentiginosis. Patients are exposed to mechanical and bleeding complications. It is a cancer predisposition syndrome. Our study highlights the diagnostic criteria for Peutz-Jeghers syndrome (SPJ), the complications and the therapeutic progresses in patient care. We report the case of a 32-year-old male presenting with a massive melaena. It was hospitalized in the surgical intensive care unit with hypovolemic shock difficult to control. This required surgical intervention to stop bleeding. We found a hamartomatous polyps in the small intestine which caused bleeding. Peutz Jeghers Syndrome was diagnosed on the basis of labial lentigines during childhood. Clinical and paraclinical explorations did not reveal the presence of cancer. In Madagascar, this disease is still poorly understood. In the literature, the diagnosis of Peutz Jeghers syndrome is based on clinical findings or on the presence of complications such as haemorrhage, invagination or bowel obstruction. In our case, the disease was complicated by gastrointestinal bleeding with hypovolemic shock. Endoscopic polypectomy using double-balloon enteroscopy can reduce emergency small bowel surgery. Peutz-Jeghers syndrome is a rare disease. Despite this, it is important for clinicians to know it and to take it into consideration in case of gastrointestinal bleeding.